Evidenzbasierte, interdisziplinäre Behandlung der abdominellen Sepsis = Evidence-based interdisciplinary treatment of abdominal sepsis - Schmoch, Thomas; Saeedi, Mohammed al; Richter, Daniel; Brenner, Thorsten; Hackert, Thilo; Weigand, Markus A. (Der Chirurg, 2019)
Abdominal sepsis is the most severe form of abdominal infection. It is characterized by a dysregulated host response to infection leading to life-threatening organ failure or septic shock. The latter has a mortality of >40%. This article reviews the evidence on the strategic approach to treatment of patients with abdominal sepsis and septic shock. The focus is on the time-critical elements of diagnosis, anti-infective treatment and hemodynamic stabilization.
Gesehen am 07.10.2019